Globe-LFMC 2.0, an enhanced and updated dataset for live fuel moisture content research - Yebra, Marta (2024)
Globe-LFMC 2.0, an updated version of Globe-LFMC, is a comprehensive dataset of over280,000 Live Fuel Moisture Content (LFMC) measurements. These measurements weregathered through field campaigns conducted in 15 countries spanning 47 years. In contrastto its prior version, Globe-LFMC 2.0 incorporates over 120,000 additional data entries,introduces more than 800 new sampling sites, and comprises LFMC values obtained fromsamples collected until the calendar year 2023. Each entry within the dataset providesessential information, including date, geographical coordinates, plant species, functionaltype, and, where available, topographical details. Moreover, the dataset encompassesinsights into the sampling and weighing procedures, as well as information about land covertype and meteorological conditions at the time and location of each sampling event. Globe-LFMC 2.0 can facilitate advanced LFMC research, supporting studies on wildfire behaviour,physiological traits, ecological dynamics, and land surface modelling, whether remotesensing-based or otherwise. This dataset represents a valuable resource for researchersexploring the diverse LFMC aspects, contributing to the broader field of environmental andecological research.